Strategi Pengembangan Makanan Unggulan Minangkabau Berdaya Saing Global - Rosalina, Eka; Wirahadi Ahmad, Afridian; Dwi Haryadi, Anda (Akuntansi dan Manajemen, 2015)
This research aims to discuss the development strategies of traditional minangkabau food which became pre-eminent in West Sumatra Province. Tours in the Minangkabau is known in three things namely culinary tour (traditional foods), nature tourism and cultural tourism. The technique of data collection through interviews and questionnaires as well as FGD. Data analysis was done with the analysis tools SWOT, EFAS, IFAD da QSPM. The object of the traditional food flagship developed is the beef rendang. The results of the analysis of internal factors obtained score 3.1 while external factor analysis of the retrieved value score 2.8. This indicates that the product is able to maintain the same power factor-factor exists to be able to overcome his weakness factors. In addition to the main development strategy that is right based on the internal-external matrix is keep and preserve consisting of market penetration strategies and product development strategy. While based on analysis of the QSPM retrieved the most priority strategy is a strategy of improving and maintaining the image quality of the products and packaging as well as food quality control. While the next alternative strategies is to increase promotion and different types of products.